Comparative Study Of Professionalism Of Future Medical Doctors Between Malaysia And Bangladesh - Salwani, Ismail; Iza, A. Rahman; Mainul, Haque (2014)
Every profession has its particular social responsibilities. Thus. professionalism is the foundation of medicine's indenture with humanity. The schooling and refinement of professionalism has long been part of medical education. Recently professionalism is recognized as a fundamental qualification in both developed and developing countries. The objective of this study was to scrutinize and compare the professionalism of medical students of Malaysia and Bangladesh. This was Cross-sectional study conducted on 1208 Year-I to Year-V MBBS students of session 2011-2012 and 2012-2013. from Malaysia and Bangladesh. Data was collected using a validated instrument. Only 42% respondents were male and the rest 58% were female. Total mean professionalism scores for male was 177.57 and female was 175.82. Again total score of professionalism of Malaysia and Bangladesh were 175.50 and 177.14 respectively. Significant differences observed between gender (p=0.026) and country (3=0.044) in total scores of elements of professionalism. The present study found there has almost equal level of understanding on principal humanistic concems of professionalism. Between gender and country there are significant differences. Professionalism should be incorporate in undergraduate and postgraduate medical course curriculum. Henceforth. communities will have rational prescriber for the common marginalized people. © 2014 Md. Zakirul Islam et al.